Atorvastatin versus placebo in patients with covid-19 in intensive care: randomized controlled trial. (7th January 2022) - ,
Abstract: Objective: To assess the effect of statin treatment versus placebo on clinical outcomes in patients with covid-19 admitted to the intensive care unit (ICU). Design: INSPIRATION/INSPIRATION-S was a multicenter, randomized controlled trial with a 2×2 factorial design. Results for the anticoagulation randomization have been reported previously. Results for the double blind randomization to atorvastatin versus placebo are reported here. Setting: 11 hospitals in Iran. Participants: Adults aged ≥18 years with covid-19 admitted to the ICU. Intervention: Atorvastatin 20 mg orally once daily versus placebo, to be continued for 30 days from randomization irrespective of hospital discharge status. Main outcome measures: The primary efficacy outcome was a composite of venous or arterial thrombosis, treatment with extracorporeal membrane oxygenation, or all cause mortality within 30 days from randomization. Prespecified safety outcomes included increase in liver enzyme levels more than three times the upper limit of normal and clinically diagnosed myopathy. A clinical events committee blinded to treatment assignment adjudicated the efficacy and safety outcomes. Results: Of 605 patients randomized between 29 July 2020 and 4 April 2021 for statin randomization in the INSPIRATION-S trial, 343 were co-randomized to intermediate dose versus standard dose prophylactic anticoagulation with heparin based regimens, whereas 262 were randomized after completion of the anticoagulation study. 587 of the 605 participants were included in the primary analysis of INSPIRATION-S, reported here: 290 were assigned to atorvastatin and 297 to placebo (median age 57 years (interquartile range 45-68 years); 256 (44%) women). The primary outcome occurred in 95 (33%) patients assigned to atorvastatin and 108 (36%) assigned to placebo (odds ratio 0.84, 95% confidence interval 0.58 to 1.21). Death occurred in 90 (31%) patients in the atorvastatin group and 103 (35%) in the placebo group (odds ratio 0.84, 95% confidence interval 0.58 to 1.22). Rates for venous thromboembolism were 2% (n=6) in the atorvastatin group and 3% (n=9) in the placebo group (odds ratio 0.71, 95% confidence interval 0.24 to 2.06). Myopathy was not clinically diagnosed in either group. Liver enzyme levels were increased in five (2%) patients assigned to atorvastatin and six (2%) assigned to placebo (odds ratio 0.85, 95% confidence interval 0.25 to 2.81). Conclusions: In adults with covid-19 admitted to the ICU, atorvastatin was not associated with a significant reduction in the composite of venous or arterial thrombosis, treatment with extracorporeal membrane oxygenation, or all cause mortality compared with placebo. Treatment was, however, found to be safe. As the overall event rates were lower than expected, a clinically important treatment effect cannot be excluded. Trial registration: ClinicalTrials.gov NCT04486508.